ANALISIS KADAR ENZIM SGPT MENCIT TERINFEKSI Plasmodium berghei UNTUK MENETAPKAN AKTIVITAS GAMBIR LAUT (Clerodendrum inerme ) SEBAGAI HEPATOPROTEKTIF - Pattimura, Nadira; PATTIMURA, NASTAIN ABUBAKAR (Pasapua Health Journal, 2023)
Introduction : Malaria, caused by the Plasmodium parasite transmitted by Anopheles mosquitoes, remains a serious health problem in Indonesia and throughout the world. Research on the effect of Gambir Laut leaf extract on malaria and its impact on liver damage is very important in overcoming the spike in malaria cases in Indonesia.Method: This research is a laboratory experiment.Results: The results of measuring SGPT enzyme levels showed that the administration of Gambir Laut infusion extract could reduce SGPT enzyme levels in mice infected with Plasmodium berghei ANKA. The lowest SGPT levels were in the group of infected mice that were only given a 10% dose of Sea Gambir extract.Conclusion: Based on the results of this study it can be concluded that administration of Gambir Laut infusion extract at doses of 01.%, 1% and 10% in mice infected with Plasmodium berghei ANKA can reduce levels of the SGPT enzyme.